Formulasi Substrat Dasar Kotoran Sapi dan Limbah Cair Tempe dengan menggunakan Inokulum Rumen Sapi Untuk Studi Awal Produksi Biogas - Bidayanti Ruru; Umrah Umrah; Orryani Lambui (Biology Department, Mathematics and natural science, Tadulako University, 2018)
The research of “Biogas Production by Utilizing of Basic Substrate of Fermented Liquid waste of tempeh and Cow Waste by Using Inoculum from Cow Rumen” for the basic study of biogas production was held on May until July 2016 at department Biology Laboratory unit Biotechnology, Faculty of Mathematic and Natural Sciences, University of Tadulako. The purposed of this research is to produce biogas by utilizing the basic of liguid waste of tempeh and cow waste, and also to know the concentration of using the rumen inoculum of cow rumen. This research is designed with completely randomized design which consists of six treatment with three repeating. the basic substance are composed of 500 grams of cow dung and 500 ml of liquid waste tempe.The composition of treatment is : ( P0 100% Basic Substrate Without inoculum), ( P1 80% Basic Substrate + 20% inoculums) ,(P2 60% Basic Substrate + 40% inoculums), (P3 40% Basic Substrate + 60% inoculums) , (P3 20% Basic Substrate + 80% inoculums), (P5 100% inoculum Without basic substrate). Observation variable are consist of biogas volume measuring, pH measuring, light test and temperature measuring. anaerobic fermentation process is carried out in a culture bottle with a volume of 1000 ml bottle mouth top covered with a balloon for gas storage. The results of this research show that Biogas could be produced by using the basic substrate of fermented liguid waste of tempeh and cow waste with the inoculum from cow rumen, at, P2, P3, dan P4 treatment. The highest volume of gas in P2 treatment (60% Basic Substrate : 40% inoculum) which has 553,33 cm3. The pH which in the culture is about 6,33-6,46 and the result flame with temperature in 152ºC.